Comparison of fibronectin in human marginal gingiva and interdental papilla using immunohistochemistry - Mohammad Tavakoli; Ensiyeh Bateni; Fazeleh Attarbashi-Moghadam; Ardeshir Talebi; Jaber Yaghini; Ahmad Mogharehabed (Wolters Kluwer Medknow Publications, 2011)
Background: The differences between marginal gingiva and interdental papilla may be due to variation in the molecular composition of these two different anatomical structures. The aim of this study was to evaluate the staining intensity of fibronectin in human marginal gingiva and interdental papilla. Materials and Methods: In a prospective analytical study, 16 healthy subjects needing crown lengthening surgery were selected. All participants were medically healthy, non-smokers, with no medication intake, and a healthy periodontium. During surgery, facial/buccal marginal gingiva and interdental papilla were separately harvested. The specimens were subjected to hematoxylin and eosin, histochemical (Masson' strichorom, reticulin, and elastic), and immunohistochemical staining for evaluation of morphology and inflammation; assessment of connective tissue fibers (collagen, reticulin, and elastic); and determination of fibronectin staining intensity. The data were analyzed by Spsssoftware, Wilcoxon, and Spearman tests. P<0.05 was considered to be statistically significant. Results: From a total of 32 specimens, 21 specimens were found to be normal or having mild inflammation, while the remaining specimens had moderate to severe inflammation in some parts. Collagen fibers were found to be dense in reticular connective tissue and degenerated in the region of inflammation. Reticulin fibers strongly stained near epithelium. Elastic fibers were sparsely found. Mean fibronectin staining intensity between marginal gingiva and interdental papilla was not statically significant (P=0.44). There is no statistically significant correlation between tissue inflammation and fibronectin staining intensity (P=0.76 for marginal gingival and P=0.20 for interdental papilla). Considering all specimens, fibronectin staining intensity of connective tissue adjacent to Sulcular/Junctional epithelium was higher than reticular connective tissue (P=0.003) and higher than connective tissue adjacent to oral epithelium (P<0.001). Conclusion: This study did not show any difference in interdental papilla and marginal gingival with respect to fibronectin composition. More studies in this context are needed.